2013
DOI: 10.1080/15433714.2012.663673
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Admission to a Day School Treatment Program

Abstract: In this study the authors examine the individual and family characteristics of youth (N = 105) admitted over a five year period to a day school treatment program in a western New York community. All had exhausted alternative school placements within their home school districts and had a history of severe emotional or behavioral problems. Consistent with national patterns, more males (78%) than females were admitted, but in contrast to national trends, more Caucasians (63.8%) than students of color (36.2%) were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 31 publications
(44 reference statements)
1
0
0
Order By: Relevance
“…The results support the known risk factors of male sex and lower social status (21,22), while more than two years in nursery school/kindergarten was associated with a reduced risk. A study from the USA showed that quality of child care has a positive effect on the cognitive and language skills before starting school (23).…”
Section: Resultssupporting
confidence: 81%
“…The results support the known risk factors of male sex and lower social status (21,22), while more than two years in nursery school/kindergarten was associated with a reduced risk. A study from the USA showed that quality of child care has a positive effect on the cognitive and language skills before starting school (23).…”
Section: Resultssupporting
confidence: 81%